Rapidly Progressive Corticobasal Degeneration Syndrome - Ana Herrero Valverde; Sónia Costa; Ângela Timoteo; Ricardo Ginestal; José Pimentel (Case Reports in Neurology, 2011)
Introduction: Corticobasal syndrome (CBS) has a heterogeneous clinical presentation with no specific pathologic substratum. Its accurate diagnosis is a challenge for neurologists; in order to establish CBS definitively, postmortem confirmation is required. Some clinical and radiological features can help to distinguish it from other neurodegenerative conditions, such as Creutzfeldt-Jakob disease (CJD). Clinical Case: A 74-year-old woman presented with language impairment, difficulty in walking and poor attentiveness that had begun 10 days before. Other symptoms, such as asymmetrical extra-pyramidal dysfunction, limb dystonia and ‘alien limb’ phenomena, were established over the next 2 months, with rapid progression. Death occurred 3 months after symptom onset. Laboratory results were normal. Initially, imaging only showed restricted diffusion with bilateral parieto-occipital gyri involvement on DWI-MRI, with unspecific EEG changes. An autopsy was performed. Brain neuropathology confirmed sporadic CJD (sCJD). Conclusions: CBS is a heterogeneous clinical syndrome whose differential diagnosis is extensive. CJD can occasionally present with clinical characteristics resembling CBS. MRI detection of abnormalities in some sequences (FLAIR, DWI), as previously reported, has high diagnostic utility for sCJD diagnosis – especially in early stages – when other tests can still appear normal. Abnormalities on DWI sequencing may not correlate with neuropathological findings, suggesting a functional basis to explain the changes found.